Novel Matrix Normalization Technique for Accurate LC‐ESI‐MS/MS Detection and Quantification of Drugs and Their Metabolites in Toxicology Research and Practice. Issue 1 (9th January 2023) - Rosano, Thomas G.; Rumberger, John M.; Scholz, Kiley L.; Konetchy, Robert M.; Wood, Michelle
Abstract: Accurate identification and quantification of drugs and their metabolites (analytes) in biological matrices is an analytical foundation of clinical and forensic toxicology. For decades, liquid chromatography interfaced by electrospray ionization with tandem mass spectrometry (LC‐ESI‐MS/MS) has been a widely used technology for analysis in the field of toxicology, as well as in many other fields of bioscience. It is also known that ion response in LC‐ESI‐MS/MS analysis is influenced by coeluting biological compounds and that preanalytical sample clean‐up is often insufficient in removing these interferences. As a result, a normalization technique is commonly used for assessment and compensation of matrix effects encountered in routine analysis. Internal standardization with a stable isotope analog of the analyte is the predominant normalization technique used in LC‐ESI‐MS/MS analysis. The technique, however, requires commercial availability or costly custom synthesis of an isotopic analog specific for each analyte. Here we describe an alternative technique for matrix normalization for use in high‐volume, multianalyte testing without the need for isotope analogs. The technique involves analysis of the original sample (neat analysis) followed by analysis of a second sample aliquot (spike analysis) that has been fortified with a controlled amount of reference analyte. A calibration procedure similar to internal standardization is employed, using an ion response ratio of neat to fortified analyte. As a demonstration of the technique in multianalyte testing, we provide a detailed protocol for simultaneous detection and quantification of 102 drugs and drug metabolites in human urine. We also provide a support protocol for addition of new analytes to the multianalyte panel, allowing convenient collection of the validation data during routine testing. The matrix normalization technique and testing principles may be applicable to a wide range of analytes and biological matrices, not only those encountered in toxicology but also in other fields of bioscience. © 2023 Wiley Periodicals LLC. Basic Protocol : Detection and quantification of 102 toxicology analytes in urine by LC‐ESI‐MS/MS analysis using the threshold accurate calibration technique Support Protocol : Method for addition and validation of new analytes to expand the Basic Protocol